An Analytical Solution for the Two-Layered Composite Beam-Column with Interlayer Slip and Constant Axial Load - Ecsedi, István; Baksa, Attila; Lengyel, Ákos József; Gönczi, Dávid (International Journal of Engineering and Management Sciences, 2023)
The authors present an analytical solution for the two-layered composite beams with imperfect shear connections. The considered beam is simply supported at both ends. The beam is subjected to transverse and axial loads. The kinematic assumptions of the Euler-Bernoulli beam theory are used. The connection of the beam components is perfect in normal direction, but the axial displacement field may have jump. The shear axial force derived from the imperfect connection is proportional to the relative slip occurring between the layers. The determination of the analytical solution is based on the Fourier method. Two examples illustrate the application of the presented analytical method.